A study on fashion street in Beijing- Through street fashion and its images - YONGLI HAO; EUN-YOUNG SHIN (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: Beijing is one of the top Chinese fashion cities, and this research focuses on the fashion streets of Guomao and Sanlitun in this area.Method: To do so, they analyzed and researched their own fashion street images, as well as the four influential factors that create images of street fashion: social backgrounds (inferred from bibliographic data), physical environments (based on observation), surrounding factors (including human and cultural factors), and fashion consciousness (based on a survey).Findings: This research demonstrates that while Guomao has matured into an affluent and tranquil fashion street catering to adults, Sanlitun has evolved into a hip and happening fashion street catering to young adults. However, both locations have relatively recent histories, making it questionable whether or not their respective street cultures emerged organically. Usually, a city’s street culture is what gives it its identity, but Beijing’s fashion streets were designed that way by the government. In other words, policy factors played an extremely critical role, and they dominated other factors that distinguish Beijing’s fashion streets from those in other developing countries. This is in addition to the social backgrounds, physical environments, surrounding factors, and human and cultural factors shown by many previous studies.Implications/Novel Contribution: The data gathered in this study can serve as a model for other developing nations’ economic and cultural advancement.